2021
DOI: 10.3390/mi12060606
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Plasma Electrolytic Processing and Mechanical Polishing for Single-Crystal 4H-SiC

Abstract: Single-crystal 4H-SiC is a typical third-generation semiconductor power-device material because of its excellent electronic and thermal properties. A novel polishing technique that combines plasma electrolytic processing and mechanical polishing (PEP-MP) was proposed in order to polish single-crystal 4H-SiC surfaces effectively. In the PEP-MP process, the single-crystal 4H-SiC surface is modified into a soft oxide layer, which is mainly made of SiO2 and a small amount of silicon oxycarbide by plasma electrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Electrolyte plasma was successfully applied to the precision polishing of single-crystal SiC in our previous research. Experimental results showed that the MRR can be greatly improved with low surface roughness by a combination of plasma electrolytic processing and mechanical polishing for single-crystal 4H-SiC [89,90]. Ultrasonic-assisted polishing could improve the polishing efficiency and quality.…”
Section: Electrolyte Plasma Polishing (Epp)mentioning
confidence: 99%
“…Electrolyte plasma was successfully applied to the precision polishing of single-crystal SiC in our previous research. Experimental results showed that the MRR can be greatly improved with low surface roughness by a combination of plasma electrolytic processing and mechanical polishing for single-crystal 4H-SiC [89,90]. Ultrasonic-assisted polishing could improve the polishing efficiency and quality.…”
Section: Electrolyte Plasma Polishing (Epp)mentioning
confidence: 99%
“…Также есть исследования методик ХМП GaAs с использованием абразивного ледяного диска [81], с абразивом TiO 2 при ультрафиолетовом (УФ) облучении [82]. На примере 4Н-SiC исследуется методика планаризации поверхности, где кремний переводят в окисленное состояние путем плазменно-электролитического оксидирования с последующим удалением оксида абразивным составом [83]. Такой метод окисления предполагает перенос обрабатываемой пластины из электролитической ячейки на полировальник, что обуславливает трудность масштабирования технологии.…”
Section: обрабатыunclassified
“…The analysis results of the oxide surface composition and Si 2p spectra indicated that the formation of SiO x C y and SiO 2 took place during the oxidation process. 50 Similarly, in 2021, Ma et al 51 combined Plasma-Electrolytic Processing and Mechanical Polishing (PEP-MP). It can be observed that the hardness of the single-crystal 4H-SiC surface underwent a significant reduction from 2,891.03 to 72.61 HV after PEP.…”
Section: Fine Chemical Engineering Volume 4 Issue 2|2023| 283mentioning
confidence: 99%